The Author’s Worldview in the Novel Teruslah Bodoh Jangan Pintar by Tere Liye - Nuzulia, Hilda; Supriyanto, R.M. Teguh (Universitas Jambi, Magister Program of English Education Department, 2026)
This research aims to describe the author's worldview in the novel